Rosmarinic Acid in Underground Parts of Different Mentha Species - Mergová M.; Balažová A.; Mučaji P.; Bittner Fialová S. (Sciendo, 2023)
Mints (Mentha L., Lamiaceae) are medicinal plants frequently used in pharmacy, cosmetics, and food industry. Among the secondary metabolites found in mint, rosmarinic acid is one of the most abundant in the whole plant. Rosmarinic acid is known as a powerful antioxidant and anti-inflammatory agent.